أثر القيادة التحويلية على ديناميكية الجماعة في المؤسسة - هارون ،سميرة; عرابي ،محفوظ (جامعة الوادي University of Eloued, 2024)
This study aimed to analyze the relationship and clarify the impact of transformational leadership in its basic dimensions on group dynamics in the economic institution, with a case study of a sample of economic institutions in the state of Bouira. The descriptive analytical approach was relied upon for its suitability to the objectives of the study, with the help of the statistical program "SPSS" in order to analyze the data and information collected through the questionnaire distributed to a sample of 250 workers. The study concluded that the correlation coefficient (R) between transformational leadership and group dynamics reached 0.897 at a significance level (α≤ 0.05), and with a coefficient of determination (R2) of 0.805. The study also concluded that the level of significance for the functional and personal variables is greater than the significance level (α≤ 0.05), which indicates the absence of statistically significant differences in the answers of the study sample members about group dynamics in the institutions under study attributed to personal and functional variables.
The impact of transformational leadership on group dynamics in the enterprise: A case study of a sample of economic enterprises
Keywords: قيادة; قيادة تحويلية; جماعة العمل; ديناميكية الجماعة; مؤسسة اقتصادية; Leadership; transformational leadership; work group; group dynamics; economic